Researches in architecture teaching, project didactics and professional training (Research, Society and Development, 2022)
The project teaching has been conceptualized by numerous researchers as an educational process that is broader than the simple transmission of techniques and information. This article aims to debate didactic issues and outline procedures to track evidence of the formation of professional architects in project teaching contexts. The methodology includes analyzing implications of Didactics approaches for the daily project teaching and its relationship with professional training in architecture. The results show the argument that different approaches to teaching-learning processes provided by the field of Didactics have direct implications for pedagogical practices in Architectural Project. Limits of concepts and procedures are explained in the analysis of the relationship between Didactics and different trends in project teaching. The article concludes by emphasizing that this reflection stimulates the preliminary bases for an object under construction, articulating research in architecture education, project didactics and professional training for future architects.